A Review on Respiratory Health Effects with High Pollution Biomass Fuels - Dr. Kishore Kumar Soni*, Moina sharma, Dr. Sindhuparva Rana (Innovative Journal of Medical and Health Sciences, 2020)
An acute respiratory infection sadly contributes to the foremost reasons for the deaths worldwide.A systematic secondary data research was conducted using Scopus database and MEDLINE according to for Systematic Reviews Meta-Analyses and preferred reporting items.Case–control or cross-sectional designs were used in the study. Quantifiable or reported were provided for approximation of the alliance between COPD and biomass released smoke with analogous 95% CI in female; and they were based on a free set of data from other studies.Air contamination in houses excessively has a massive impact on the health of women and children. This is a prominent reason of deaths worldwide. Though this area of study usually remains unnoticed, it affects a large section of the world’s populace. Key words: respiratory infection–COPD–biomass Fuels–Systematic Reviews